Hubungan Kekuatan Iklan Frestea Green di Televisi terhadap Respon Konsumen Berdasarkan Model Hierarki Efek - Budi Astuti; Sri Yeni (Universitas Islam Indonesia, 2007)
In the era of high competition, companies are required to develop effective communication programs. This research article reveals that there is a significant correlation between consumer responses based on hierarchical effects through the advertisement power on television. Five of seven variables of advertisement power, as independent variables, have been the most closely connection with the consumer responses based on the model of hierarchical effects. Of these five variables, the variable of frequency of the on air advertisement has been the most closely connection with the consumer responses. Keywords: Advertisement power, consumer responses, hierarchical effect model.